Effect of Aloe vera extract for reducing formaldehyde level in tuna fish for halal and thoyyib food - Subhan Rullyansyah; Fitrotin Azizah; Baterun Kunsah (Universitas Airlangga, 2020)
This study aims to determine the effect of Aloe vera extract in reducing formaldehyde levels in tuna processed into